Pengaruh Penerapan Project Based Learning terhadap Keterampilan Berpikir Kritis dan Kreatif serta Prestasi Menulis Siswa - Hasanah, Uswatun (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
The development of critical and creative thinking abilities are two 21st-century skills that university graduates are expected to possess in addition to their proficiency in writing. In order for pupils to thrive and compete in the disruptive age, these two abilities are crucial. The goal of the current research is to better understand how the PBL model affects L1 writing performance, critical thinking, and creative thinking abilities, despite the fact that there have been several experimental studies employing the BL model in writing instruction. This research employed a sequential mix-method design, with a qualitative approach in the last phase and a quantitative approach in the first. Questionnaires, evaluation rubrics, essay writing examinations, and interviews were used to gather the data. The researcher then performed one-way ANCOVA and paired sample t-tests to provide a quantitative analysis of the data. Additionally, the researcher used theme analysis approaches to examine data from semi-structured interviews. When compared to traditional models utilized in the control class, the PBL model demonstrated that students could greatly enhance their writing performance, critical thinking abilities, and creative thinking capabilities. Additionally, by demonstrating that students had favorable attitudes and opinions about learning to write, the interview results supported the quantitative findings. Put another way, because they were inspired to learn to write, kids who received instruction using the PBL paradigm responded positively and had a positive attitude.